The impact of a slow interplanetary coronal mass ejection on Venus. Issue 5 (12th May 2015) - Collinson, Glyn A.; Grebowsky, Joseph; Sibeck, David G.; Jian, Lan K.; Boardsen, Scott; Espley, Jared; Hartle, Dick; Zhang, Tielong L.; Barabash, Stas; Futaana, Yoshifumi; Kollmann, Peter
Abstract We present Venus Express observations of the impact of a slow interplanetary coronal mass ejection (ICME), which struck Venus on 23 December 2006, creating unusual quasi steady state upstream conditions for the 2 h close to periapsis: an enhanced (∼ nT) interplanetary magnetic field (IMF), radially aligned with the Sun‐Venus line; and a dense (∼ cm−3) solar wind. Contrary to our current understanding and expectations, the ionosphere became partially demagnetized. We also find evidence for shocked sheathlike solar wind protons and electrons in the wake of Venus, and powerful (≈ nT2/Hz) foreshock whistler mode waves radiating from the bow shock at an unexpectedly low frequency (0.6 Hz). Given the abnormally high density of escaping heavy ions at the magnetopause boundary (295 cm−3, one of the highest of the whole mission) and the enhanced density of escaping heavy ions in the wake, we find that even weak ICMEs with no driving shocks can increase atmospheric loss rates at Venus and suggests that the Bx component of the IMF may be a factor in atmospheric escape rates.